Harmonic analysis of the torque of the YAMZ-5340 engine - Yu. P. Makushev; T. A. Polyakova (Омский научный вестник)
The purpose of the study is to find a technique and conduct on its basis a harmonic analysis of the torque of an internal combustion engine for the subsequent determination of resonant vibrations of the crankshaft. The method of calculating the harmonics of the engine torque is given on the example of a YaMZ-5340 diesel engine with a power of 100 kW at a crankshaft rotation speed of 2300 min-1. Based on the results of thermal and dynamic calculation of the YaMZ-5340 engine, a graph of changes in its torque is constructed and harmonics of the first and second orders are calculated. The frequencies of natural and forced vibrations of the crankshaft and its resonant critical rotation frequency are determined. The number of the torque harmonic has been determined, which, according to the frequency of forced vibrations, coincides with the frequency of natural vibrations and causes resonance. The results of the study can be applied in the design and fine-tuning of engines in order to calculate and reduce torsional vibrations.